Branch Retinal Vein Occlusion with Complications of Vitreus Bleeding Performed by Vitrectomy and Endolaser - Faika Novadianaz; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2018)
Introduction. Retinal vein occlusion is the largest group of retinal blood vessel abnormalities after diabetic retinopathy. Macular edema and neovascularization are major complications in BRVO that require therapy. Vitrectomy is indicated in cases of vitreous hemorrhage that fail spontaneous resolution after 6 weeks to 3 months. The time to do vitrectomy depends on the tendency of the ophtalmologist and the patient's visual needs. Case Presentation. A woman, 59 years old, housewife, came to the Eye Clinic on July 2016. The main complaint history is that the right eye has become more blurred since ± 2 months ago. On examination of the posterior segment of the right eye the detail is difficult to assess. In this patient suspected turbidity of the vitreous cavity so that an ultrasound examination was performed. Vitreous bleeding is an indication for vitrectomy. Intraoperatively after the vitrectomy, bleeding and ghost vessels were found in the super-temporal region. Conclusion. The main goals of therapy in BRVO are to improve hemodynamics, overcome macular edema, and prevent neovascularization.